2008
DOI: 10.2478/s11532-008-0045-0
|View full text |Cite
|
Sign up to set email alerts
|

Sol-gel preparation and characterization of non-substituted and Sr-substituted lanthanum cobaltates

Abstract: This paper reports on the results concerning the sol-gel preparation and characterization of Sr-substituted perovskite lanthanum cobaltates La 1-x Sr x CoO 3-d (x = 0.0, 0.25, 0.5 and 0.75). The metal ions, generated by dissolving starting materials in diluted acetic acid were complexed by 1,2-ethanediol to obtain the precursors for the non-substituted and Sr-substituted LaCoO 3 . The influence of the synthesis temperature, heating time and the amount of substituent on the phase purity of La 1-x Sr x CoO 3-d w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
(71 reference statements)
1
8
0
Order By: Relevance
“…All the diffraction peaks of samples calcined at 500-700°C are well matched with La 0.7 Sr 0.3 FeO 3 (JCPDS 89-1269), respectively, except a small peak located at 25.2°( 2h) corresponding to SrCO 3 phase (JCPDS 05-0418). This phenomenon was also observed by Karpinski et al [22,23]. Most of the alkaline earth metal oxides and rare earth metal oxides, in particular BaO, SrO, and Re 2 O 3 , contain metal carbonate [24,25].…”
Section: Methodssupporting
confidence: 52%
“…All the diffraction peaks of samples calcined at 500-700°C are well matched with La 0.7 Sr 0.3 FeO 3 (JCPDS 89-1269), respectively, except a small peak located at 25.2°( 2h) corresponding to SrCO 3 phase (JCPDS 05-0418). This phenomenon was also observed by Karpinski et al [22,23]. Most of the alkaline earth metal oxides and rare earth metal oxides, in particular BaO, SrO, and Re 2 O 3 , contain metal carbonate [24,25].…”
Section: Methodssupporting
confidence: 52%
“…These findings agree with literature data obtained by X‐ray diffraction. Cizauskaite and Kareiva investigated LSC samples with different Sr‐concentrations also fabricated by a sol‐gel process 37. They demonstrated that a single‐phase perovskite is formed at calcination temperatures between 900 and 1000 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Cizauskaite and Kareiva investigated LSC samples with different Sr-concentrations also fabricated by a sol-gel process. [ 37 ] They demonstrated that a single-phase perovskite is formed at calcination temperatures between 900 and 1000 ° C. At lower temperatures they found the formation of metastable phases like Co 2 O 3 , SrCO 3 [ 38 ] La 2 CoO 4 is also known to be formed if the perovskite-type LaCoO 3 is reduced at high temperatures. [ 39 ] wileyonlinelibrary.com The grayscale histogram of the image stack of sample LSC800 is displayed in Figure 4 c. It shows the voxel frequency in dependence of the grayscale value.…”
Section: Crystalline Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of approaches such as solid-state reactions (Zhou et al, 2006), mechanical-synthesis (Szabo et al, 2002), coprecipitation (Nakayama et al, 2003;Srdic et al, 2005), solution combustion or thermal decomposition (Bansal and Zhong, 2006;Berger et al, 2004;Berger et al, 2007) hydrothermal, and sol-gel technique (Pechini, 1967;Cizauskaite and Kareiva, 2008) have been used to synthesize LaMO 3 -based perovskite powders. The solgel method is highly attractive because various metal ions are chelated to form metal complexes in solution and are uniformly distributed at the molecular level.…”
Section: Introductionmentioning
confidence: 99%